Gambaran Kemauan Siswa Sekolah dalam Pemberian Pertolongan Pertama Cedera - Rida Darotin (Jurnal Kesehatan dr. Soebandi, 2023)
Background: Injury is a health problem caused by accident. Age 5-14 years is a period of growth and development to develop gross motor skills which have a high risk of injury. Tens of millions of children require treatment every year due to injuries, most of these cases experience life-long disabilities. School-age children, namely 6 years of age, have a higher assumption of their physical abilities, while 7-12 years of age have limitations in understanding related to self-safety. Methods: This research is a descriptive study that aims to describe the willingness to perform first aid on 238 grade VIII students at SMPN 1 Jember using a total sampling technique. The inclusion criteria in the study were that students were willing to become respondents, and were present when the research was carried out. Exclusion criteria in this study were respondents in an unhealthy condition, permission not attend school. The instrument has been analyzed for validity and reliability tests with a confidence level of 0.05 using 20 samples. Results: Most of the respondents in the study were 13 years old with the most female sex. For the category of willingness to provide first aid in the category of moderate willingness. Some students are willing to provide and determine the tools needed, try to find information, carry out consultations, and provide calm to provide assistance. And in the category only willing to spend time and allocate funds to provide assistance. Conclusion: it is necessary to provide continuous information so that the introduction of first aid programs for injuries can be considered as something that is really needed by everyone in an effort to instill a will to reduce morbidity due to injuries.